2010
DOI: 10.1093/hmg/ddp589
|View full text |Cite
|
Sign up to set email alerts
|

CTCF binding is not the epigenetic mark that establishes post-fertilization methylation imprinting in the transgenic H19 ICR

Abstract: Imprinted expression of the mouse Igf2/H19 locus is controlled by parent-of-origin-specific methylation of the imprinting control region (ICR). We previously demonstrated that when placed in a heterologous genomic context, the H19 ICR fragment contains an intrinsic activity that allows it to acquire differential methylation in somatic cells but not in germ cells. In the present study, we investigated the requirements for the CTCF-binding sites of the ICR in the acquisition of post-fertilization methylation. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 33 publications
1
23
0
Order By: Relevance
“…The unmethylated state of the transgenic H19 ICR did not change even at embryonic day (E) 8.5, despite the fact that allele-nonspecific methylation, probably elicited by postimplantation de novo DNA methylation activity, was observed outside of the DMR (Fig. 1G) (Matsuzaki et al, 2010). These results demonstrated that the paternally inherited transgenic H19 ICR must be recognized by the DNA methylation machinery, including DNMT3A and DNMT3L, in early embryos to acquire imprinted methylation.…”
Section: Methylation Acquisition At the Transgenic H19 Icr In Early Ementioning
confidence: 82%
See 3 more Smart Citations
“…The unmethylated state of the transgenic H19 ICR did not change even at embryonic day (E) 8.5, despite the fact that allele-nonspecific methylation, probably elicited by postimplantation de novo DNA methylation activity, was observed outside of the DMR (Fig. 1G) (Matsuzaki et al, 2010). These results demonstrated that the paternally inherited transgenic H19 ICR must be recognized by the DNA methylation machinery, including DNMT3A and DNMT3L, in early embryos to acquire imprinted methylation.…”
Section: Methylation Acquisition At the Transgenic H19 Icr In Early Ementioning
confidence: 82%
“…Another possibility is that an epigenetic mark to designate its paternal origin might be set in this region of the H19 ICR during spermatogenesis. Importantly, this is the first example of regulatory sequences that ensure a stable methylation level of the paternal H19 ICR during preimplantation periods, because all the cis regulatory elements identified to date (such as CTCF or Sox-Oct binding motifs) function to maintain the unmethylated state of maternal H19 ICR following implantation (Matsuzaki et al, 2010;Sakaguchi et al, 2013;Schoenherr et al, 2003;Zimmerman et al, 2013).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…1B, top). It is established that in the absence of CTCF binding sites the maternally inherited H19 ICR fragment cannot maintain its hypomethylated state in somatic cells and becomes hypermethylated after implantation, both in the endogenous locus (22) and in transgenic contexts (34). Therefore, we speculated that an unmodified DNA fragment would be hypermethylated eventually, even if it were once hypom-ethylated by the aid of H19 ICR sequences.…”
Section: Generation Of Yac-tgm Bearing Chimeric H19 Icr Sequencesmentioning
confidence: 98%